View driven inter-organisational workflows. (1st January 2012) - Tahamtan, Amirreza; Eder, Johann
We propose a layered architecture for choreographies and orchestrations of web services. The proposed architecture uses the concept of process views. The distributed nature of the model and the concept of views improve the privacy of business partners but do not limit their interaction capabilities, an essential feature in B2B and inter-organisational applications. Our approach enables description of business processes in different levels of detail with a uniform modelling language and is fully distributed.